A Novel Homozygous Variant in GJA1 Causing a Hallermann-Streiff/Oculodentodigital Dysplasia Overlapping Phenotype: A Clinical Report - Jimenez-Armijo, Alexandra; Oumensour, Khadja; Bousfiha, Bouchra; Rey, Tristan; Laugel-Haushalter, Virginie; Bloch-Zupan, Agnès; El Arabi, Samira (Frontiers in Dental Medicine, 2021)
This paper reports the case of a Moroccan girl with a phenotype within the clinical spectrum of both Hallermann-Streiff (HSS, OMIM 234100) and Oculodentodigital Dysplasia (ODDD, OMIM 164200) syndromes. The patient presented with repeated dental abscesses and severe early childhood caries. She had no learning deficit nor psychomotor regression; however, a language delay was noted. She also presented with obstructive sleep apnea syndrome and specific craniofacial features pathognomonic of HSS. Radiographic examination showed enamel and dentin defects, giving a ghost-like tooth appearance. Several clinical features of ODDD overlap those of HSS and may confuse diagnosis, considering that the inheritance of HSS is not described yet. The diagnostic odyssey of this patient ended with the identification by exome sequencing of a novel homozygous alteration in the GJA1 gene. A missense substitution in exon 2 [Chr6(GRCh37): g.121768554C>G NM_000165.4: c.561C>G p.Cys187Trp] was identified by whole-exome sequencing (WES), suggesting a diagnosis of ODDD. This is the first report of a homozygous mutation affecting the second extracellular loop of the CX43 protein.